Caracterização do recobrimento do aço SAE 4130 com Inconel 625 utilizando processos de soldagem TIG e LASER - Piatto, Augusto de Moraes [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The union of nickel superalloy and steel compliment the best properties of each other and make extreme condition applications possible. This is evident when considering the oil and gas industry, drilling tools, connectors and applications that require great mechanical resistance, and chemical corrosion resistance. With that scope, this study's intent is to compare the coating methods of Inconel 625 on steel SAE 4130 by TIG and LASER welding, in microstructures, microhardness and wear, using an optical microscope, Vickers test, and standard ASTM G65, respectively. The microstructure and the microhardness tests were performed using the specimen with both welding methods, TIG and LASER, while the wear test was not possible to be performed due to the lack of specimen. It was noted that the interdendritic spacing and HAZ (Heat Affected Zone) showed a greater difference by the two methods used, where higher values were shown by TIG, while for LASER, these values were about eight times and twenty-five times smaller, respectively. By consequence, the average hardness result from the specimen's profile was smaller, while superficial hardness values were extremely high, due to hardening. The wear test performed in the specimen of TIG method showed reliable and reproducible results, with loss of mass of 0,843g for five minutes and 1,463g during ten minutes of testing. The difference in both methods caused bigger microstructures, with bigger interdendritic spaces and formations of secondary arms for TIG welding. Due to the smaller cooling rate, this affects the micro and macro hardness grain refining, and consequently, its wear. Care was needed for the machining of the specimen after coating because it was responsible to generate a hard, thin surface layer. In regards to its own thickness, it hasn't affected the analysis of the whole ... (Complete abstract click electronic access below)

A união de superligas de níquel e aço complementa as melhores propriedades umas das outras e torna possível aplicações em condições extremas. Isto é evidente quando se considera a indústria de petróleo e gás, ferramentas de perfuração, conectores e aplicações que exigem grande resistência mecânica e à corrosão química. Com esse escopo, a intenção deste estudo é comparar os métodos de revestimento do Inconel 625 em aço SAE 4130 por soldagem TIG e LASER, em microestrutura, microdureza e desgaste, utilizando microscópio ótico, teste Vickers e ensaio ASTM G65, respectivamente. Os testes de microestrutura e dureza foram realizados com o espécime com os dois métodos de soldagem, TIG e LASER, enquanto o teste de desgaste não foi possível devido à falta de amostra. Observou-se que o espaçamento interdendrítico e a ZTA apresentaram maior diferença pelos dois métodos utilizados, onde valores mais altos foram mostrados pelo TIG, enquanto que para o LASER esses valores foram cerca de oito vezes e vinte e cinco vezes menores, respectivamente. Consequentemente, o resultado médio de dureza do perfil da amostra foi menor, enquanto os valores de dureza superficial foram extremamente altos, devido ao encruamento. O teste de desgaste realizado na amostra do método TIG mostrou resultados confiáveis e reprodutíveis, com perda de massa de 0,843g por cinco minutos e 1,463g durante dez minutos de teste. A diferença em ambos os métodos causou microestrutura maiores, com maiores espaçamentos interdendríticos e formações de braços secundários para soldagem TIG. Devido à menor taxa de resfriamento, isso afeta o refinamento de grãos, micro e macrodureza e, consequentemente, seu desgaste. Foi necessário cuidado para a usinagem da amostra após o revestimento, porque foi responsável por gerar uma camada... (Resumo completo, clicar acesso eletrônico abaixo)
Characterization of SAE 4130 with Inconel 625 steel coating using TIG and LASER welding processes
Keywords: Aço de alta resistência; Ligas de níquel; Solda e soldagem; Dureza; Steel, High strength